Electrochemical investigations of H2-producing enzymes - Goldet, G (2009)
Hydrogenases are a family of enzyme that catalyses the bidirectional interconversion of H+ and H2. There are two major classes of hydrogenases: the [NiFe(Se)]- and [FeFe]-hydrogenases. Both of these benefit from characteristics which would be advantageous to their use in technological devices for H2 evolution and the generation of energy. These features are explored in detail in this thesis, with a particular emphasis placed on defining the conditions that limit the activity of hydrogenases when reducing H+ to produce H2. Electrochemistry can be used as a direct measure of enzymatic activity; thus, Protein Film Electrochemistry, in which the protein is adsorbed directly onto the electrode, has been employed to probe catalysis by hydrogenases. Various characteristics of hydrogenases were probed. The catalytic bias for H2 production was interrogated and the inhibition of H2 evolution by H2 itself (a major drawback to the use of some hydrogenases in technological devices to produce H2) was quantified for a number of different hydrogenase. Aerobic inactivation of hydrogenases is also a substantial technological limitation; thus, inactivation of both H2 production and H2 oxidation by O2 was studied in detail. This was compared to inhibition of hydrogenases by CO so as to elucidate the mechanism of binding of diatomic molecules and determine the factors limiting inactivation. This allows for a preliminary proposal for the genetic redesigning of hydrogenases for biotechnological purposes to be made. Finally, preliminary investigation of the binding of formaldehyde, potentially at a site integral to proton transfer, opens the field for further research into proton transfer pathways, the structural implications thereof and their importance in catalysis.